Knowledge, attitues and experiences of clients regarding voluntary counselling and testing at Mankweng primary health care facilities Capricorn District Limpopo Province - Ramoraswi, Manku Magdeline (My University, 2009)
Please refer to the document
Thesis (MPH.) --University of Limpopo, 2009
Keywords: Voluntary counselling and testing; HIV/Aids; Health screening; Multiphasic health screening; Patient self-monitoring